Amapeza and Nigripeza, new genera of Neotropical micropezid flies (Diptera, Micropezidae, Taeniapterinae) - Marshall, Stephen A. (Zootaxa, 2022)
The new Neotropical genera Amapeza and Nigripeza are described for seven new species and three named species previously treated as part of the genus Grallipeza Rondani. Amapeza includes A. amazonica (Enderlein) new combination, A. affinis (Hennig) new combination, A. hyaloptera (Hendel) new combination and the new species A. camelina A. plicata, and A. tricincta. Nigripeza includes N. obscura (Hennig) new combination and the new species N. cali, N. octa and N. spangleri.